Pilot field trial of the EG95 vaccine against ovine cystic echinococcosis in Rio Negro, Argentina: 8 years of work (Veterinary Science, 2018)
Cystic echinococcosis is endemic in the Rio Negro province ofArgentina. After 30 years of control using praziquantel in dogs,the transmission rate to humans and sheep has decreased significantly,however transmission persistsThe objective of the study is to assess the impact of the inclusionof the EG95 vaccine in sheep in the control program.The vaccine was applied to lambs from communities of nativepeoples which included 70 producers (Anecón Grande, MamuelChoique, Nahuel Pan y Río Chico Abajo).From 2009 on, lambs received two doses of the EG95 vaccinewhen they were 30 and 60 days of age, followed by a singlebooster injection when the animals were 1 year of age. Thetransmission of Echinococcus granulosus was assessed throughnecropsy in mature sheep, Arecoline test and coproantigen testin dogs and register of new clinical cases in inhabitants of thearea. A total of 29.323 doses of EG95 vaccine were applied tolambs in the 2009-2017 period, working with 4 groups of 2 veterinarieseach, covering 83.5% with one doses, 80.1% with twodoses and 85.7% with three doses. Before the vaccine was introduced,in necropsy of sheep of 6 years old showed that 45.7%were infected with E. granulosus. The rate decreased to 21.1% in2006. The number of cysts per animal decreased from 1.4% to0.3. The number of producers with infected animals decreasedfrom 84.2% to 22.2%. The humoral response to the vaccination,in field conditions, showed an increased in antibodies with thesecond dose, reaching its maximum after the booster at one yearof age for many years and keeping constant.In dogs, 4.7% was found positive using arecoline purgationand 20.3% of the farms were infected using coproantigen test.The impact assessment showed a 5.6% of dogs positive to thearecoline test. Only a new case of echinococcosis was detectedin kids with a 10 cm cyst, and its origin was probably before thevaccination. EG95 vaccine has been effective to prevent the infectionin ovines up to six years of age, in spite of the difficultiesof achieving better coverage. The transmission to dogs and humanbeings has to be determined.
Keywords: echinococosis; vaccine EG95; sheep; control; prevalence